Hubungan Antara Tingkat Self-compassion dan Risiko Academic Burnout pada Mahasiswa di Fase Penyusunan Skripsi - Naraya Kinastrian Siniddhikara Duarsa; Astri Anggraini Hapsara Wibowo; Roswiyani Roswiyani (CV. Rayyan Dwi Bharata, 2025)
This study examines the relationship between self-compassion and academic burnout among final-year undergraduate students at University who are completing their theses. Academic burnout has become a significant concern due to prolonged academic stress, while self-compassion is recognized as an internal coping mechanism that may mitigate such stress. Using a quantitative correlational design, data were collected from 240 respondents through purposive sampling. Participants completed the Self-compassion Scale (SCS) and the Academic Resilience Scale-30 (ARS-30), both measured using a four-point Likert scale. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) with Spearman’s Rho correlation test due to non-normal data distribution. The results revealed a strong negative and significant correlation between self-compassion and academic burnout (rs = –0.762, p < 0.05), indicating that higher self-compassion levels are associated with lower academic burnout. These findings highlight the protective role of self-compassion in reducing academic exhaustion and emotional fatigue among students facing academic pressure. The study concludes that enhancing self-compassion may serve as an effective psychological strategy to prevent academic burnout in higher education contexts.